Misfortune Seldom Comes Alone: Evidence from Typhoon Effects During COVID-19 Quarantines in the Philippines - YINGXUE JIN; MAKIKO NAKAMURO; YASUYUKI SAWADA; ANDREW S. GRIFFEN; TSEND-AYUSH SOSORBARAM; YUKICHI MANO (Asian Development Review)
This study examines the effect of a typhoon on low-income urban neighborhoods in the Philippines during the coronavirus disease quarantine. Using household panel data, we assess welfare—as measured by psychological distress, food consumption, and human capital investment—exploiting cross-sectional variation in flood exposure and the unintended timing of interviews relative to the typhoon. The typhoon did not exacerbate food insecurity during the strict quarantine period; in fact, flooded households ate more than nonflooded households over the next 2 months, presumably due to flood relief. Parents in flooded households initially experienced less psychological distress immediately after the flooding but accumulated more distress than nonflooded parents over the next 2 months. The typhoon also reduced the home-study time of high school students. These findings highlight the need for flood risk reduction and targeted interventions to address the lingering mental health effects of extreme weather events in vulnerable populations.